Aborsi dalam Konteks Kekerasan Seksual: Implikasi Hukum Islam dan Perlindungan Korban - Gusti Meidyna Nafiazka; Fathia Rizki Maulana; Mutia Audini (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Pregnancy caused by forced sexual intercourse is a very difficult issue for women, especially for Muslim women. Due to a lack of knowledge about the permissibility of abortion in the context of sexual violence with a focus on the implications of Islamic law, Muslim women as victims, their families, and medical professionals face difficulties in making informed decisions on this issue. The purpose of this article is to analyze the Islamic legal perspective on abortion in these circumstances and examine the legal protections available to victims of sexual violence. In addition, the article examines the characteristics of mothers and infants as living beings, with particular emphasis on the distinction between the right to life of the fetus and the right to health and well-being of the mother. The article provides suggestions for the harmonization of victim protection laws and policies using a multidisciplinary approach. It also provides recommendations for the harmonization of laws, victim protection policies, and the provision of comprehensive health services, to ensure a balance between justice and the protection of human rights.